STATISTICAL EVALUATION ON THE EFFECTS OF ROTATION SPEED IN HYBRID MICRO WIRE ELECTRICAL DISCHARGE TURNING - Firdauz, M.; Izamshah, R.; Akmal, M.; Kasim, M.S.; Ding, S. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Demand for micro parts fabrication are steadily increase in today's manufacturing technology. Conversely, the traditional manufacturing process through re-sizing and scaling down the machine tools and equipment will affect the component accuracy especially for small difficult-to-machine materials. For that reason, in this study an electrical spark erosion process is adopted to deal with the discrepancy for micro size components manufacturing. This process is synonym with the name of wire electrical discharged turning (WEDT) which incorporates a turning process of rotating workpiece to continuous travelling electrode wire in electrical discharged conditions produced by wire electrical discharge machine. However, incorporating wire EDM to remove material in symmetrical cylindrical shape component causing several challenges especially with regards to the process stability. One of the most important factors that will effect on the WEDT machining performances is the rotational spindle speed. Therefore, knowledge and understanding on the effects of WEDT rotation speed towards part performances namely surface roughness (Ra) and material removal rate (MRR) are necessitate for the success of machining. Based on the experimental results, it was found that increasing rotational spindle speed does not improve MRR. In contrast, by employing high spindle speed capable to produce fine surface roughness on part machined surface. It revealed that an increment in workpiece circumferential length causing an augmentation cumulative of spark region. This phenomenon has increased the energy intensity per unit length as the number of arc regions are increased.